2009
DOI: 10.1007/s11709-010-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated modeling system for improved multi-objective reservoir operation

Abstract: Reservoir is an efficient way for flood control and improving all sectors related to water resources in the integrated water resources management. Moreover, multiobjective reservoir plays a significant role in the development of a country's economy especially in developing countries. All multi-objective reservoirs have conflicts and disputes in flood control and water use, which makes the operator a great challenge in the decision of reservoir operation. For improved multi-objective reservoir operation, an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
6
0
4
Order By: Relevance
“…The VEM progressively manages the available S , increasing the outflows as the S decreases. Given the reservoir inflow at time i (I ), and by assuming a constant inflow in the future, the number of intervals left (n) until the reservoir runs out of S are given by Equation (2):…”
Section: Vemmentioning
confidence: 99%
See 1 more Smart Citation
“…The VEM progressively manages the available S , increasing the outflows as the S decreases. Given the reservoir inflow at time i (I ), and by assuming a constant inflow in the future, the number of intervals left (n) until the reservoir runs out of S are given by Equation (2):…”
Section: Vemmentioning
confidence: 99%
“…Flood management aims to guarantee dam safety, minimize downstream floods, and maintain the full operational capacity of reservoirs once a flood is over [1][2][3][4][5]. Dams with gated spillways represent around 30% of large dams around the world [6], and provide more possibilities for water conservation and flood abatement than those with fixed-crested spillways [7].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization techniques are generally used for planning, designing and assessing effectiveness of a flood control measure. Traditional and nontraditional optimization models such as Linear Programming, Non Linear Programming, Genetic algorithms, Fuzzy logic and Neural Networks models have been extensively used in planning and evaluating efficiency of flood control systems (Wasimi and Kitanidis, 1983;Unver and Mays, 1990;Chandramouli and Raman, 2001;Wang et al 2010;Ferreira and Teegavarapu, 2012;Fu et al 2014). Some of the model applications in river system flood control studies can be found in the works of Needham et al (2000), Braga and Barbosa (2001) and Hsu (2007 and2008).…”
Section: Introductionmentioning
confidence: 99%
“…The authors evaluated the performance of these three models and concluded that the SLP model can be used for planning purposes similar to the LP model but with faster convergence, whereas the NLP model can provide the most accurate and suitable results, particularly for real-time operations. The application of a multi-objective optimization technique coupled with a hydrologic model was developed by Wang et al (2010), who combined a global optimization system with a distributed biosphere hydrologic model coupled with reservoir routing model. The application of these models to simulate the operation of Hoa Binh Reservoir in China resulted in the significant reduction of peak flood at a downstream control point and increased reservoir levels after the simulation period, which can be beneficial for future water supply (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%